Research of Pneumatic Polishing Force Control System Based on High Speed On/off with PWM Controlling - Dong, Jinlong; Shi, Jiashun; Liu, Cong; Yu, Tianbiao (Robotics and computer-integrated manufacturing, 2021)
•Reliability force control is required by polishing process.•A pneumatic polishing force control system is designed on a 5-DOF hybrid robot.•High speed on/off valve controlled by PWM signals is applied by the system.•The polishing force control system presents excellent effectiveness and stability.•The system can work at an adaptive status for different force requirements. In the polishing process, contact force has obvious influence on material removal rate, thus realizing stability and effectiveness of force control is a significant issue for automatic polishing. This paper designs a pneumatic polishing force control system to achieve reliability force control. The system is based on a high speed on/off valve which is controlled by Pulse-Width Modulation (PWM) signals. PWM signals are generated by a Programmable Logic Controller (PLC). Proportion-Integration-Differentiation (PID) control algorithm with moving average filter is conducted in the PLC, thus dynamic property of the system has been improved. The pneumatic system is assembled on a 3-TPS hybrid robot with 5 degrees of freedom (DOF) movement to equip a polishing experimental platform. Polishing force control experiments are conducted on the experimental platform to research the performances and characteristics of the pneumatic polishing force system. According to the experimental results, the pneumatic system presents excellent effectiveness and response speed to track a certain desired polishing force value with small force tracking error. Percentage of absolute average errors are descending as the desired force values is increasing, and settling time is small enough for the polishing manufacture. Therefore, based on the high speed on/off valve, the pneumatic polishing force system proposed in this paper can be conducted in various polishing processes and satisfy special requirements of different workpieces. The polishing force control system can be adjusted to work at an adaptive status due to the excellent effectiveness, stabilization and response speed of force tracking.